(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Larsen syndrome is a rare inherited disorder characterized by congenital dislocation of multiple joints along with other anomalies of heart, face, hands and bones. Larsen syndrome was first described in 1950 by Larsen, Schottstaedt and Bost. In the present report, we describe a 10 year old girl who presented with mid facial hypoplasia with depressed nasal bridge, high arched palate, bilateral talipes equinovarus and high arched feet. On examination, she had short stature (HAZ -3.5 SD) with hyperextension of knee joint, fixed flexion of elbow joint. Awareness of this condition and associated complications may help in management and follow up of these patients.